Tensile resistances of bolted circular flange connections. (15th September 2018) - Couchaux, Maël; Hjiaj, Mohammed; Ryan, Ivor; Bureau, Alain
Highlights: Experimental tests and numerical analysis are performed on bolted circular flange connections in tension. Bolt preloading and initial flange openings influence evolution of bolt forces. A full analytical model is proposed to evaluate the tensile resistance of bolted circular flange connections. Simplifications are proposed for the position of the prying force. Abstract: A closed form solution for the ultimate tensile resistance of a bolted flange joint is derived considering yield line failure mechanisms developed by Igarashi et al. The position of the prying force is determined based on formulations previously developed by the authors. Under various simplified assumptions and approximations, a design approach similar to that of the Eurocode 3 for T-stubs is proposed. To validate this approach, experimental tests have been performed on six connections of circular hollow sections made of bolted ring flange. A finite element model considering the elastoplastic behaviour of steel and contact conditions has been developed and the results showed a good agreement with experimental results. Based on the FEM model, a parametric study shows that the proposed analytical model is valid for a wide range of connections.